WORKING CAPITAL MANAGEMENT MODEL IN WOMEN'S COOPERATIVES - Achmad Murdiono; Imam Mukhlis; Arief Noviarakhman Zagladi (Transpublika Publisher, 2023)
The presence of Women's Cooperatives or also known as